2010
DOI: 10.1051/0004-6361/201014177
|View full text |Cite
|
Sign up to set email alerts
|

The molecular environment of the Galactic star forming region G19.61–0.23

Abstract: Context. Although current facilities allow the study of Galactic star formation at high angular resolution, our current understanding of the high-mass star-formation process is still very poor. In particular, we still need to characterize the properties of clouds giving birth to high-mass stars in our own Galaxy and use them as templates for our understanding of extragalactic star formation. Aims. We present single-dish (sub)millimeter observations of gas and dust in the Galactic high-mass star-forming region … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…In fact, this cloud is the only in our sample that is experiencing a merger/collision at this particular timeframe, where a long filamentary cloud, v /R), as a function of gas surface density Σ for all resolved GMCs extracted from the H 2 densities as circles (grey being inter-arm clouds, and black being arm clouds). The light-green triangles are a compilation of Galactic GMCs, while the dark-green star symbols are GMCs from extragalactic studies (from Rosolowsky et al 2003;Rosolowsky 2007;Bolatto et al 2008;Heyer et al 2009;Rathborne et al 2009;Santangelo et al 2010;Wong et al 2011;Swinbank et al 2011;Ginsburg et al 2012;Wei et al 2012;Giannetti et al 2013;Battersby et al 2014;Colombo et al 2014;Walker et al 2015). The dashed curves show the expected force balance (kinetic, gravitational and external pressure), for different values of external pressure, from P = 1 to 100 M pc −3 km 2 s −2 (which corresponds to P/k ∼ 5 × 10 3 − 5 × 10 5 K cm −3 ).…”
Section: High Velocity Dispersion Cloudsmentioning
confidence: 99%
“…In fact, this cloud is the only in our sample that is experiencing a merger/collision at this particular timeframe, where a long filamentary cloud, v /R), as a function of gas surface density Σ for all resolved GMCs extracted from the H 2 densities as circles (grey being inter-arm clouds, and black being arm clouds). The light-green triangles are a compilation of Galactic GMCs, while the dark-green star symbols are GMCs from extragalactic studies (from Rosolowsky et al 2003;Rosolowsky 2007;Bolatto et al 2008;Heyer et al 2009;Rathborne et al 2009;Santangelo et al 2010;Wong et al 2011;Swinbank et al 2011;Ginsburg et al 2012;Wei et al 2012;Giannetti et al 2013;Battersby et al 2014;Colombo et al 2014;Walker et al 2015). The dashed curves show the expected force balance (kinetic, gravitational and external pressure), for different values of external pressure, from P = 1 to 100 M pc −3 km 2 s −2 (which corresponds to P/k ∼ 5 × 10 3 − 5 × 10 5 K cm −3 ).…”
Section: High Velocity Dispersion Cloudsmentioning
confidence: 99%
“…G19.61−0.23 is a well-known region of high-mass star formation in the Galaxy, containing OH (Caswell & Haynes 1983) and CH 3 OH masers (Caswell et al 1995;Walsh et al 1998), including the rare 9.9 GHz CH 3 OH maser (Voronkov et al 2010), cold dust continuum emission (Walsh et al 2003;Thompson et al 2006), molecular line emission (Santangelo et al 2010) and multiple ultracompact (UC) H II regions (Garay et al 1998). Kolpak et al (2003) determined a distance to G19.61−0.23 of 12.3 kpc, based on HI observations.…”
Section: Nhmentioning
confidence: 99%
“…5.3 for details). For comparison, the density of points in this plot from a compilation of extragalactic cloud samples (from Rosolowsky et al 2003;Rosolowsky 2007;Bolatto et al 2008;Santangelo et al 2010;Wong et al 2011;Wei et al 2012;Colombo et al 2014) and a compilation of Galactic cloud samples (from Heyer et al 2009;Rathborne et al 2009;Wang et al 2009;Ginsburg et al 2012;Giannetti et al 2013;Battersby et al 2014;Walker et al 2015) are shown with blue contours, and with blue colour shading, respectively. The green dotted curves show the expected force balance between kinetic, gravitational and external pressure, for different values of external pressure, from P = 1 to 100 M pc −3 km 2 s −2 (which corresponds to P/k ∼ 5 × 10 3 − 5 × 10 5 K cm −3 ).…”
Section: Propertymentioning
confidence: 99%